"The Best Pope the Jews Ever Had": Jewish Reactions to the Death of Pope John Paul II - Watson, Murray (Studies in Christian-Jewish Relations, 2013)
With the death of Pope John Paul II in April 2005, the world lost what was arguably the most prominent and respected voice in the Jewish-Christian relationship in the late twentieth and early twenty-first centuries. John Paul was widely loved and appreciated by the Jewish community, for his life-long friendship with the Jewish people, and his consistent commitment to advancing Jewish-Catholic dialogue and uprooting antisemitism in all its forms. His death, therefore, sparked a torrent of eloquent tributes from Jewish leaders and spokespersons, both in Israel and throughout the Diaspora, highlighting his major accomplishments and historic gestures, and frankly acknowledging areas in which he had sometimes been at the center of disagreements, frictions and conflict with his “beloved elder brothers.” Through a re-visiting of a cross-section of published Jewish comments from the time of John Paul’s death, this article examines something of the complexity and challenges of the Jewish-Catholic relationship during his papacy, and discusses how, over the course of his nearly 27-year papacy, John Paul II became (at least for many people) “the best Pope the Jews ever had.”